DEVELOPMENT OF ZAKAT, INFAQ, AND SHODAQOH APPLICATION SYSTEMS IN MOSQUES IN THE COMMUNITY - Hani Fitria Rahmani; Febri Dolis Herdiani (DIA: Jurnal Administrasi Publik, 2021)
Continuing the previous research with the title "The Influence of Trust and Application of Zakat Application Technology on Community Interest in Zakat", the background of the current research is based on the results of previous research which states that the application of zakat application technology has a greater influence on zakat interest than trust. The next step is the process of developing zakat application technology, it is hoped that it can collect people's funds more easily, especially in mosques that are more spread out in public and have high levels of flexibility in cash flows. It is hoped that the development of the zakat application in this research will make it easier for muzakki to distribute their zakat, infaq, and sodaqoh funds and provide transparency for the distribution of community funds received by Mustahik in mosques, especially mosques in the wider community. This research method begins with research and development of application users in this case Muzakki and Mustahik, then system design, system development, testing, and then documenting. The results of this study are the formulation of technology concepts and their applications which serve as literature material for the government and interested parties for decision making on the development of the zakat application system as well as reference material for further research to carry out updates on zakat information technology that have an impact on the welfare of the people.